2011
DOI: 10.1080/00087114.2002.589779
|View full text |Cite
|
Sign up to set email alerts
|

Development and Programmed Cell Death in the Filament Cells of Lathyrus undulatus Boiss.

Abstract: -The androecium in Lathyrus undulatus Boiss. consisted of 10 stamens. The anther was joined to the fi lament on the outward facing surface (dorsifi xed). After dehiscence anther and fi lament separate from connecting edge and anther falls off. In the present study development and programmed cell death process in the fi lament cells of Lathyrus undulatus Boiss. (Fabaceae) were analyzed by light, fl uorescence and electron microcopy, during pollen development. The observations indicated that fi lament cells most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…A previous study on filament cells of Lathyrus undulatus Boiss showed that after pollen maturation, the filament is separated from the anther via degeneration of the connecting edge so anthers can fall off (Filiz and Meral 2011).…”
Section: Atcep1 Localizes To the Connecting Edge Of Anther And Filamentmentioning
confidence: 99%
“…A previous study on filament cells of Lathyrus undulatus Boiss showed that after pollen maturation, the filament is separated from the anther via degeneration of the connecting edge so anthers can fall off (Filiz and Meral 2011).…”
Section: Atcep1 Localizes To the Connecting Edge Of Anther And Filamentmentioning
confidence: 99%
“…Researchers have been detected the TUNEL positive reaction in cells undergoing PCD such as in filament of Hordeum vulgare (Wang et al 1999), in tapetal cells of Zea mays (González-Sanchez et al 2004) and, in suspensor and endosperm of Phaseolus coccineus (Lombardi et al 2007). Also, TUNEL positive nuclei were detected in anther wall cells and filament of Lathyrus undulatus (Vardar and Ünal 2012)…”
Section: Discussionmentioning
confidence: 96%
“…During dPCD processes, researchers have been reported the vacuolization in the inner integument of Brassica napus (Wan et al 2002), in tapetal cells of Oryza sativa (Ku et al 2003) and in tapetum and filament of Lathyrus undulatus (Vardar and Ünal 2012). Besides, vacuolization was reported during dPCD processes ofstyle tissue of Ficus carica (Aytürk and Ünal 2018), stigma of Arabidopsis thaliana (Gao et al 2018), and anther and ovule of Opuntia robusta (HernandezCruz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations